Design and implementation of an Arduino-based instrument for parabolic motion. Issue 1 (January 2021) - Sesa, E; Labania, H M D; Darwis, D; Ismail, M; Badaruddin,; Maskur,; Ulum, M S
Abstract: The lack of a physical instrument for determining the initial speed of experiment of the parabolic motion in the Department of Physics, Tadulako University, is one problem. In this research, we have been designed, implemented, and tested to show the initial velocity value of an Arduino-based to address this problem. The stages of this research began with the design and manufacture of mechanical systems, electronic systems such as power supply circuits and infrared detector circuits, motor stepper circuit, a series of servo motors, LCD circuits, and keypad circuits using the Arduino ATmega 2560 microcontroller. The next stage is making the test program and the main program. This tool has been tested and operated so that it gets good results. The initial measured speed is displayed on the LCD. The stability of measuring objects is excellent based on a low standard deviation between 0.02 - 0.06.